A Survey on Content Delivery of Web-Pages - Bashir, Aaqib; Gurav, TH (International Journal of Computer Sciences and Engineering, 2025)
Content delivery networks (CDNs) play an important role in today’s Internet. They serve a large multimedia data over the Internet and resolve the issues of scalability and network congestion. The content providers are no longer the sole generators of the content in CDN system but user are also involved. User generated content (UGC) is emerging as one of the dominant forms in the multimedia industry and is reshaping the way users watch video, with millions of content producers and consumers. In particular, multimedia sites are creating new viewing patterns and social interactions that influence the way users consume data. There also exists various techniques such as collaborative caching, context-aware recommendations, etc. that can help in efficient content delivery. In this paper, we present a survey on various techniques and methods employed in the delivery of multimedia content. We present a way to optimize the system performance, and characterizing the tradeoff between cost and quality of service in content delivery.